A matched comparison of the patient-reported outcome measures of 38,716 total and unicompartmental knee replacements: an analysis of linked data from the National Joint Registry of England, Northern Ireland and Isle of Man and England’s National PROM collection programme - Hasan R Mohammad (Taylor & Francis Group, 2021)
Background and purpose — The surgical treatment options for severe knee osteoarthritis are unicompartmental (UKR) and total knee replacement (TKR). For patients, functional outcomes are more important than revision rate. We compared the patient-reported outcome measures (PROMs) of both implant types using a large PROMs dataset. Patients and methods — We analysed a propensity-matched comparison of 38,716 knee replacements (19,358 UKRs and 19,358 TKRs) enrolled in the National Joint Registry and the English National PROM collection programme. Subgroup analyses were performed in different age groups. Results — 6-month postoperative Oxford Knee Score (OKS) for UKR and TKR were 38 (SD 9.4) and 36 (SD 9.4) respectively. A higher proportion of UKRs had an excellent OKS (≥ 41) compared with TKR (47% vs 36%) and a lower proportion of poor OKS (< 27) scores (13% vs. 16%). The 6-month OKS was higher in all age groups for UKR compared with TKR, with the difference increasing in older age groups. The mean 6-month EQ-5D score was 0.78 (SD 0.25) and 0.75 (SD 0.25) respectively. The improvement in EQ-5D resulting from surgery was higher for UKR than TKR both overall and in all age groups. All comparisons were statistically significant (p < 0.05). Interpretation — UKR had a greater proportion of excellent OKS scores and lower proportion of poor scores than TKR. Additionally, the quality of life was higher for UKR compared with TKR. These factors should be balanced against the higher revision rate for UKR when choosing which procedure to perform.